Analysis Of Red Chili Farming Income: Case Study on Kiria A Farmer Group in Bhera Village, Mego District, Sikka Regency (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the income and feasibility of red chili (Capsicum annuum L.) farming in the Kiria A Farmer Group in Bhera Village, Mego District, Sikka Regency. The research method used is a case study with a qualitative and quantitative approach. Data was collected through interviews with all members of the farmer group as many as 25 people as respondents. Analysis was carried out on the components of fixed costs, variable costs, total revenue, net revenue, and business feasibility through the calculation of the R/C ratio. The results of the study show that the average total production cost is IDR 3,889,000 per planting season, while the total income reaches IDR 30,000,000. Thus, the net income obtained by farmers is IDR 26,111,000. The R/C ratio value of 7.71 (>1) indicates that red chili farming is feasible and profitable to develop. This study provides an idea that red chili cultivation can be a potential source of income for farmers in the region if managed efficiently.